α9-Containing Nicotinic Receptors in Cancer - Pucci, Susanna; Zoli, Michele; Clementi, Francesco; Gotti, Cecilia (Frontiers in Cellular Neuroscience, 2022)
Neuronal nicotinic acetylcholine receptors containing the α9 or the α9 and α10 subunits are expressed in various extra-neuronal tissues. Moreover, most cancer cells and tissues highly express α9-containing receptors, and a number of studies have shown that they are powerful regulators of responses that stimulate cancer processes such as proliferation, metastasis, and the inhibition of apoptosis. It has also emerged that their modulation is a promising target for drug development. The aim of this review is to summarise recent data showing the involvement of these receptors in controlling the downstream signalling cascades involved in the promotion of cancer.